Heat Shock Proteins and Ferroptosis - Liu, Ying; Zhou, Lin; Xu, Yunfei; Li, Kexin; Zhao, Yao; Qiao, Haoduo; Xu, Qing; Zhao, Jie (Frontiers in Cell and Developmental Biology, 2022)
Ferroptosis is a new form of regulatory cell death named by Dixon in 2012, which is characterized by the accumulation of lipid peroxides and iron ions. Molecular chaperones are a class of evolutionarily conserved proteins in the cytoplasm. They recognize and bind incompletely folded or assembled proteins to help them fold, transport or prevent their aggregation, but they themselves do not participate in the formation of final products. As the largest number of molecular chaperones, heat shock proteins can be divided into five families: HSP110 (HSPH), HSP90 (HSPC), HSP70 (HSPA), HSP40 (DNAJ) and small HSP (HSPB). Different heat shock proteins play different roles in promoting or inhibiting ferroptosis in different diseases. It is known that ferroptosis is participated in tumors, nervous system diseases, renal injury and ischemia-reperfusion injury. However, there are few reviews about the relationship of heat shock proteins and ferroptosis. In this study, we systematically summarize the roles of heat shock proteins in the occurrence of ferroptosis, and predict the possible mechanisms of different families of heat shock proteins in the development of ferroptosis.